Automatic Vehicle Access System Using Ultra-High Frequency RFID - Poh, Priscilla Swee Pei; Rafidah Ngadengon (Journal of Electronic Voltage and Application, 2021)
Securing and monitoring the territory have become a big challenge for everyone as the number of vehicle users have increased.  The premise area must be secure with enforced entrances and exits. It should have an automated and efficient security and monitoring system. For this purpose, an automated vehicle access system with accurate and secure monitoring of vehicle entry and exit was developed with Graphical User Interface (GUI) and vehicleâ€™s user database along with the prototype of Ultra-High Frequency RFID. The suitable configuration for the hardware prototype has also been evaluated to maximize the systemâ€™s capabilities. This system operates on frequencies from 400MHz to 950MHz and is performed at distances of 7 meters. The passive tag was attached to the various condition and sizes of the car. The result shows showed that the system was optimally performed with the speed of the vehicle up to 50 km/h, 7 m of reading range and a maximum 20% tinted windshield. The ideal angle for the reader is around 60áµ’ to 70áµ’ with 2 meters of mounting pole. For future improvement, it is suggested that the registered vehicle user data was linked with the official premiseâ€™s database and the data is saved in an off-site location (cloud storage). The GUI is also able to support more than 1 reader at a time depending on demand.